A hypomorphic allele of SLC35D1 results in Schneckenbecken-like dysplasia. (19th August 2019) - Rautengarten, Carsten; Quarrell, Oliver W; Stals, Karen; Caswell, Richard C; De Franco, Elisa; Baple, Emma; Burgess, Nadia; Jokhi, Roobin; Heazlewood, Joshua L; Offiah, Amaka C; Ebert, Berit; Ellard, Sian
Abstract: We report the case of a consanguineous couple who lost four pregnancies associated with skeletal dysplasia. Radiological examination of one fetus was inconclusive. Parental exome sequencing showed that both parents were heterozygous for a novel missense variant, p.(Pro133Leu), in the SLC35D1 gene encoding a nucleotide sugar transporter. The affected fetus was homozygous for the variant. The radiological features were reviewed, and being similar, but atypical, the phenotype was classified as a 'Schneckenbecken-like dysplasia.' The effect of the missense change was assessed using protein modelling techniques and indicated alterations in the mouth of the solute channel. A detailed biochemical investigation of SLC35D1 transport function and that of the missense variant p.(Pro133Leu) revealed that SLC35D1 acts as a general UDP-sugar transporter and that the p.(Pro133Leu) mutation resulted in a significant decrease in transport activity. The reduced transport activity observed for p.(Pro133Leu) was contrasted with in vitro activity for SLC35D1 p.(Thr65Pro), the loss-of-function mutation was associated with Schneckenbecken dysplasia. The functional classification of SLC35D1 as a general nucleotide sugar transporter of the endoplasmic reticulum suggests an expanded role for this transporter beyond chondroitin sulfate biosynthesis to a variety of important glycosylation reactions occurring in the endoplasmic reticulum.